HUBUNGAN KONSEP DIRI DENGAN PERILAKU MORAL ANAK USIA DINI DI TK PERTIWI KELURAHAN SUNGAI PAKNING KABUPATEN BENGKALIS - NURHELIZA YUNIKA (Journal of Education and Teaching, 2020)
This research aims to know the level and the correlation between self concept and moral behavior of early childhood at Pertiwi Kindegarten Sungai Pakning Village Bengkalis Regency. The samples of this research were all kids age 5 – 6 years old at Pertiwi Kindegarten Sungai Pakning Village Bengkali Regency total 54 kids. The method used was Pearson Product Moment Correlation to see the correlation between self concept variable and moral behavior. The technique of data collection was observation sheet. The technique of data analysis was by using Pearson Product Moment correlational technique. From the research results, it can be recognized that the level of self concept of kids is in high category with percentage score 51,85% and the level of kids’ moral behavior is at medium category with percentage score 55,55%. Based on the result of hypothesis test, it obtains the value of correlational coefficient is in the amount of rxy = 0,837 bigger than rtable = 0,268 (0,837 > 0.268) with significance level 0,000 < 0,05. Therefore, it can be concluded that there is correlation between self concept and moral behavior. The level of the correlation is in extremely high category with the value of determinant coefficient generated is 70% then it can be recognized that self concept gives contribution 70% towards moral behavior.